Concept of women's crime and psychological features of their prevention (Zien Journal of Social Sciences and Humanities, 2022)
The article focuses on the criminological features of women's crime and provides information on their prevention. In addition, the article details the main reasons why women are now involved in crime. The level of women's crime depends on the socio-economic characteristics of different regions of the country, and women's participation in group crime is also reported.